Insights Into the Allosteric Inhibition of the SUMO E2 Enzyme Ubc9. (1st April 2016) - Hewitt, William M.; Lountos, George T.; Zlotkowski, Katherine; Dahlhauser, Samuel D.; Saunders, Lindsey B.; Needle, Danielle; Tropea, Joseph E.; Zhan, Chendi; Wei, Guanghong; Ma, Buyong; Nussinov, Ruth; Waugh, David S.; et al.
Abstract: Conjugation of the small ubiquitin‐like modifier (SUMO) to protein substrates is an important disease‐associated posttranslational modification, although few inhibitors of this process are known. Herein, we report the discovery of an allosteric small‐molecule binding site on Ubc9, the sole SUMO E2 enzyme. An X‐ray crystallographic screen was used to identify two distinct small‐molecule fragments that bind to Ubc9 at a site distal to its catalytic cysteine. These fragments and related compounds inhibit SUMO conjugation in biochemical assays with potencies of 1.9–5.8 mm . Mechanistic and biophysical analyses, coupled with molecular dynamics simulations, point toward ligand‐induced rigidification of Ubc9 as a mechanism of inhibition.